Stuck in the Middle: Fibronectin-Binding Proteins in Gram-Positive Bacteria - Hymes, Jeffrey P.; Klaenhammer, Todd R. (Frontiers in Microbiology, 2016)
Fibronectin is a multidomain glycoprotein found ubiquitously in human body fluids and extracellular matrices of a variety of cell types from all human tissues and organs, including intestinal epithelial cells. Fibronectin plays a major role in the regulation of cell migration, tissue repair, and cell adhesion. Importantly, fibronectin also serves as a common target for bacterial adhesins in the gastrointestinal tract. Fibronectin-binding proteins (FnBPs) have been identified and characterized in a wide variety of host-associated bacteria. Single bacterial species can contain multiple, diverse FnBPs. In pathogens, some FnBPs contribute to virulence via host cell attachment, invasion, and interference with signaling pathways. Although FnBPs in commensal and probiotic strains are not sufficient to confer virulence, they are essential for attachment to their ecological niches. Here we describe the interaction between human fibronectin and bacterial adhesins by highlighting the FnBPs of Gram-positive pathogens and commensals. We provide an overview of the occurrence and diversity of FnBPs with a focus on the model pathogenic organisms in which FnBPs are most characterized. Continued investigation of FnBPs is needed to fully understand their divergence and specificity in both pathogens and commensals.